2001
DOI: 10.1289/ehp.01109501
|View full text |Cite|
|
Sign up to set email alerts
|

Examination of the melatonin hypothesis in women exposed at night to EMF or bright light.

Abstract: It has been hypothesized that the increased incidence of breast cancer in industrial societies is related to greater exposure to power-frequency electric and magnetic fields (EMF) and/or the presence of high levels of light at night (LAN). EMF and LAN are said to reduce circulating levels of the hormone melatonin which, in turn, allows estrogen levels to rise and stimulate the turnover of breast epithelial stem cells and increase the risk for malignant transformation. Three laboratory-based studies, in which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(11 citation statements)
references
References 43 publications
(49 reference statements)
0
11
0
Order By: Relevance
“…28 Rotating night work may increase estrogen levels by lowering melatonin levels. 29, 30 Experimental studies corroborate this notion, and several studies lend direct 31, 32 and indirect evidence 33, 34 in support of an inverse association between melatonin and estrogen levels. Melatonin also interferes with the local synthesis of estrogens by regulating the activity of aromatases, the enzymes controlling the conversion from androgenic precursors to estrogens, thus behaving as a selective estrogen enzyme modulator or aromatase inhibitor.…”
Section: Discussionmentioning
confidence: 83%
“…28 Rotating night work may increase estrogen levels by lowering melatonin levels. 29, 30 Experimental studies corroborate this notion, and several studies lend direct 31, 32 and indirect evidence 33, 34 in support of an inverse association between melatonin and estrogen levels. Melatonin also interferes with the local synthesis of estrogens by regulating the activity of aromatases, the enzymes controlling the conversion from androgenic precursors to estrogens, thus behaving as a selective estrogen enzyme modulator or aromatase inhibitor.…”
Section: Discussionmentioning
confidence: 83%
“…13,14 In mammals, it is mainly secreted by the pineal gland during darkness, 15 and exposure to light at night may decrease plasma melatonin levels. 16 Apart from the pineal gland, studies have suggested that melatonin may be synthesized locally in the bone marrow as well as in many other tissues. 17,18 Melatonin synthesized in the bone marrow can accumulate at concentrations twice that of nocturnal blood levels, 17,19,20 which may produce strong local effects on bone.…”
Section: Introductionmentioning
confidence: 99%
“…Inconsistent exposure to light and dark, such as that experienced during shift work and rapid trans-meridian travel, disrupts entrainment and desynchronizes the internal circadian pacemaker with local sunrise and sunset (Folkard et al, 1978; Panda, 2018; Patkai et al, 1977). Failure to readapt to the local solar cycle results in an altered phase relationship between the circadian system and the sleep-wake cycle (Graham et al, 2001; Panda, 2018; Travlos et al, 2001; Zeitzer et al, 2000), which can be detrimental to sleep quantity, sleep quality, and health.…”
mentioning
confidence: 99%